Evaluation of Orthodontic Retention Protocol among Orthodontist and General Dentist-A Cross-Sectional Survey - Kumar S Ojass; Srinidhi S; Visshishta J; Sirisha Sapasetty; Ranganathan Sukanya; Priya K; Moulvi SMM (Wolters Kluwer Medknow Publications, 2024)
AimThe current study was conducted with the aim of evaluating the retention protocol followed by orthodontists in India. Material and MethodsA cross-sectional web-based questionnaire survey was carried out to evaluate the retention protocol. To determine the sample size, a pilot study was carried out, and the final sample arrived was 250 subjects. The current study's inclusion criteria took into account those who had finished their BDS&MDS (Orthodontist). ResultsThe data were statistically examined when the surveys were received and completed. The choice for fixed retainers was 67.4%. Retainer wear time preferences ranged widely, with 60% preferring 12-18 hours. The initial post-retention check appointment was planned by the majority of orthodontists (47.6%) within the next three months. Recall appointments for retention checks were only planned by the majority of orthodontists (56.3%) once every three months. Regular involvement by patients at their retention check appointments was (38%). ConclusionThe most commonly used and preferred type of retainer is fixed retainer, and dentist preferences range around 12-18 hours of wear time. Furthermore, the duration of the retainer wear preferred by most orthodontists/dentists is 10 months to 2 years.